Physicochemical and Microbiological Assays for Quality Evaluation of a Brand of Mentha piperita Tisanes in Costa Rica Market: Employment of the Central American Technical Regulation - Mora Román, Juan José (2018)
Mentha piperita is a natural hybrid of water mint (Mentha aquatica) and spearmint (Mentha spicata L.), that are consumed as tisanes. For that reason, the present work evaluated physicochemical and microbiological aspects for the quality control of a commercial brand of Mentha piperita herbal tea distributed in Costa Rica, using assays established by the Central American Technical Regulation (RTCA) 11.03.56.09 (Pharmaceutical products. Natural medicinal products for human use. Quality verification), and determined if they have uniformity for different batches of this brand. To verify the quality of three batches of this product, the following assays were done: Labeling requirements, organoleptic, minimum fill, foreign organic matter, loss on drying, total ash, acid-insoluble ash, lead and arsenic limits, microbial enumerations and specific microorganisms (E. coli and Salmonella sp.) assays. As conclusion, the batches were in compliance for all the assays, except for labeling test, since information corresponding to the primary (batch number and expiration date) and secondary packaging (qualitative-quantitative composition of active ingredients interactions and adverse effects) were not presented. Furthermore, one of the batches did not have information about the employment, contraindications and warnings. Also, the manufacturing company maintained a good reproducibility between one batch and another, and the improvements that can be made are in the product labeling and better controls in its filling.